If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10n = 9n + -9 Reorder the terms: 10n = -9 + 9n Solving 10n = -9 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 10n + -9n = -9 + 9n + -9n Combine like terms: 10n + -9n = 1n 1n = -9 + 9n + -9n Combine like terms: 9n + -9n = 0 1n = -9 + 0 1n = -9 Divide each side by '1'. n = -9 Simplifying n = -9
| x-0.7x=44 | | -4m=-8-5m | | 15(t-6)+3t=6(3t+4)-8 | | 4x+26+3x+14=180 | | 4x+5=1x-10 | | 2s+4=5(-4+2s) | | 3j/5-8J | | 5x-10=-2(x+3)-11 | | 7x+3=-2y+3 | | 2(2x-5)(6x+11)=0 | | x*.2=195 | | (.1x)+x=123343 | | 5(3x-1)/2(-2)=10 | | W=2(I+p) | | 5(3x-1)/5-2=10 | | (.05x)+x=129510 | | (7y+4)-(2+6y)=5 | | 7(x-6)+4=3x-6 | | Z^8=1 | | 5(3x-1/5(-2))=10 | | Z^9=i | | 2x(x-1)-7x=18-5(x+4) | | 21=5x+7y | | 12x(x+2)=0 | | (2x/2)=7x-1 | | 4(5x-3)+2=30 | | 6=j-88 | | X+21+2x=-12-2x-17 | | (2n-4)(3n-6)=0 | | y-1.1=-1.2 | | 10=f/3 | | x+20=43 |